Acute Sleep Restriction Has Differential Effects on Components of Attention - Cunningham, Jasmyn E. A.; Jones, Stephanie A. H.; Eskes, Gail A.; Rusak, Benjamin (Frontiers in Psychiatry, 2018)
Inadequate nightly sleep duration can impair daytime functioning, including interfering with attentional and other cognitive processes. Current models posit that attention is a complex function regulated by several separate, but interacting, neural systems responsible for vigilance, orienting, and executive control. However, it is not clear to what extent each of these underlying component processes is affected by sleep loss. The purpose of this study was to evaluate the effects of acute sleep restriction on these attentional components using the Dalhousie Computerized Attention Battery (DalCAB). DalCAB tasks were administered to healthy women (aged 19-25 years) on two consecutive mornings: once after a night with 9 h time in bed (TIB), and once again after either another night with 9 h TIB (control condition, n=19) or after a night with 3 h TIB (sleep restriction condition, n=20). Self-ratings of sleepiness and mood were also obtained following each sleep condition. Participants showed increases in self-reported sleepiness and fatigue after the second night only in the sleep restriction group. Sleep restriction primarily affected processing speed on tasks measuring vigilance; however, performance deficits were also observed on some measures of executive function (e.g. go/no-go task, flanker task, working memory). Tasks assessing orienting of attention were largely unaffected. These results indicate that acute sleep restriction has differential effects on distinct components of attention, which should be considered in modeling the impacts of sleep loss on the underlying attentional networks.